Margin Pemasaran dan Transmisi Harga Tomat di Desa Sidamangura Kecamatan Kusambi Kabupaten Muna Barat - Muhammad Hidayatullah; Idrus Salam; Abdi Abdi (Fakultas Pertanian Universitas Halu Oleo, 2022)
This study aims to analyze channel pattern and tomato marketing margins, analyze efficiency for each tomato marketing channel, and analyze tomato price transmission. To determine the sample in this study, the writer using the methods of purposive sampling and snowball sampling. Purposive sampling used for sampling all tomato farmers, so that 25 tomato farmers were obtained. Snowball sampling is used to determine marketing institutions so that 17 marketing institutions are obtained consisting of 2 collectors, 3 wholesalers, and 12 retailers. The results of the study showed that there were 3 marketing channels for tomatoes in Sidamangura Village. Channel III has the highest Farner's Share value of 73% with a total margin of Rp.2.66/Kg, so it is indicated to have the best level of marketing efficiency compared to Channel I of 60% with a total margin of Rp. 4.417/Kg and Channel II of 58% with a total margin of Rp. 5,000/Kg. Furthermore, the analysis of the price elasticity of transmission of the three channels obtained that the price elasticity of channel I is 30%, channel II is 34%, and channel III is 170%. channel III is said to be elastic because. This study aims to analyze channel pattern and tomato marketing margins, analyze efficiency for each tomato marketing channel, and analyze tomato price transmission. To determine the sample in this study, the writer using the methods of purposive sampling and snowball sampling. Purposive sampling used for sampling all tomato farmers, so that 25 tomato farmers were obtained. Snowball sampling is used to determine marketing institutions so that 17 marketing institutions are obtained consisting of 2 collectors, 3 wholesalers, and 12 retailers. The results of the study showed that there were 3 marketing channels for tomatoes in Sidamangura Village. Channel III has the highest Farner's Share value of 73% with a total margin of Rp.2.66/Kg, so it is indicated to have the best level of marketing efficiency compared to Channel I of 60% with a total margin of Rp. 4.417/Kg and Channel II of 58% with a total margin of Rp. 5,000/Kg. The elasticity of price transmission on channel I is 0.30, the elasticity of price transmission on channel II is 0.34, and the elasticity of price transmission on channel III is 0.7, the channel has elasticity < 1 or inelastic, meaning that in channel I, the price change is 1% at the retailer level will result in a 30% price change at the farmer level, channel II, which is a 1% price change at the retail level, will result in a 34% price change at the farmer level, and channel III, which is a 1% price change at the retailer level. price change of 70% at the farm level with a market shape leading to Monopsony